Discussion of "Phantom Penis: Extrapolating Neuroscience and Employing Imagination for Trans Male Embodiment". Issue 4 (1st October 2020) - Hontscharuk, Rayisa; Alba, Brandon; Schechter, Loren
ABSTRACT: As described by Straayer, the phantom penis in transgender men combines feelings of loss and potential and may contribute to self-authentication and pleasure following phalloplasty. To align their gender identity with their body, some transgender men choose to undergo a phalloplasty procedure. For the reconstructive surgeon, the goals of phalloplasty typically are summed as an aesthetically pleasing, sensate phallus with both tactile and erogenous sensation that is capable of standing micturition and penetrative intercourse. Many surgical techniques for phalloplasty have been described, with the radial forearm free flap being the most commonly used. To optimize erogenous sensation, nerve coaptation to the dorsal clitoral nerve in conjunction with burying the denuded clitoris at the base of the neophallus is often performed. While surgical technique contributes to sensory recovery, there is likely a complex interplay between physiology, anatomy, endocrinology, and psychology as they pertain to orgasm and sexuality following phalloplasty. The reconstructive surgeon should engage in a shared decision-making approach with their patient and attempt to optimize aesthetic and sensory outcomes in order to facilitate sexual function following surgery.